Measurements of size distribution of titanium dioxide fine particles in a highly concentrated non-aqueous suspension by using particle self-assembly under an electric field - Otsuki, Akira; Dodbiba, G.; Fujita, T. (Elsevier BV, 2012)
This paper describes the measurement of size distribution of TiO2 fine particles in a highly concentrated non-aqueous suspension by using self-assembly of particles under an electric field. Interactive force apparatus (IFA) was used to conduct the measurement. IFA first assembled pearl chains of particles between two electrodes, and then applied the compressive force to change the pearl chain structure by shortening the distance between electrodes. The repulsive force generated when the chain curved while the attractive force created when the chain was broken. The cycle of repulsive and attractive forces corresponds to the size of particles. The results obtained with IFA were compared with results obtained from size measurement by analyzing SEM photographs. IFA indicated the comparable results with the one obtained using SEM. The particle size distribution measured by IFA decreased as a result of increasing the supply voltages. Changes in correlation between size distribution measured by SEM and IFA at different supply voltages were observed in different size ranges. At smaller than 300 nm, result at 0.24 V fit well with the SEM result while at >600 nm gives better agreement with the results at 0.48 V. The difference is mainly due to the increase in number of particles in fine size fraction with increasing supply voltages. Decrease in size indicated that the breakage of aggregate particles and/or disintegration of doublet particles occurred due to the electrical fragmentation. The fragmentation was explained by monitoring the mean diameters and their deviation obtained from IFA measurements at different supply voltages.